2018
DOI: 10.1148/radiol.2018171544
|View full text |Cite
|
Sign up to set email alerts
|

Robotically Assisted Sonic Therapy as a Noninvasive Nonthermal Ablation Modality: Proof of Concept in a Porcine Liver Model

Abstract: Purpose To determine the feasibility of creating a clinically relevant hepatic ablation (ie, an ablation zone capable of treating a 2-cm liver tumor) by using robotically assisted sonic therapy (RAST), a noninvasive and nonthermal focused ultrasound therapy based on histotripsy. Materials and Methods This study was approved by the institutional animal use and care committee. Ten female pigs were treated with RAST in a single session with a prescribed 3-cm spherical treatment region and immediately underwent ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 26 publications
4
92
0
Order By: Relevance
“…The frequencies used in current clinically approved applications are typically below 1 MHz to further enhance the cavitation, which is inversely proportional to the frequency [97]. Although this technique has shown great potential for treating pathologies such as kidney stones [98] and liver cancer [99], its efficacy is limited to situations in which a single target can be accurately visualized and linearized prior to treatment [100]. Combined with the difficulty to image the region of interest, there is a risk of unwanted bioeffects in surrounding healthy tissue due to the high pressures (>28 MPa) required for successful procedure.…”
Section: Applications Of Acoustic Droplet Vaporizationmentioning
confidence: 99%
“…The frequencies used in current clinically approved applications are typically below 1 MHz to further enhance the cavitation, which is inversely proportional to the frequency [97]. Although this technique has shown great potential for treating pathologies such as kidney stones [98] and liver cancer [99], its efficacy is limited to situations in which a single target can be accurately visualized and linearized prior to treatment [100]. Combined with the difficulty to image the region of interest, there is a risk of unwanted bioeffects in surrounding healthy tissue due to the high pressures (>28 MPa) required for successful procedure.…”
Section: Applications Of Acoustic Droplet Vaporizationmentioning
confidence: 99%
“…Previous studies with this technology have demonstrated tissue-selective properties, suggesting that large vessels and collecting system structures may be spared, while tumors and normal parenchyma are lysed (6,7). This promising early work has led to robotic integration and development of a clinical system, resulting in Robotically Assisted Sonic Therapy (RAST) (8).…”
mentioning
confidence: 99%
“…The nonthermal nature of histotripsy is distinct from high-intensity focused ultrasound, which uses longer ultrasound pulses to create focal heating of targeted tissue (12). To date, histotripsy has been applied in a variety of large and small animal preclinical models in different organs (8,10,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to diagnostic ultrasound modalities, histotripsy-induced liquefaction zones have been visualized with MRI at field strengths between 7 and 9 T (Allen et al 2014(Allen et al , 2015Khokhlova et al 2009;Vlaisavljevich et al 2016c). Changes in the structure of media have been clearly delineated with T2-, T1-and diffusion-weighted and contrast-enhanced sequences in vitro and in vivo (Allen et al 2017;Smolock et al 2018). Lesion appearance varies based on tissue viability (in vivo vs. ex vivo) and the time at which the image is acquired relative to the histotripsy therapy.…”
Section: Quantify Changes In the Medium Caused By Bubble Activitymentioning
confidence: 99%